ASPEK HUKUM TERHADAP KEGAGALAN PELAKSANAAN PEKERJAAN KONSTRUKSI PROYEK DI JAKARTA - Kusumo Dradjad Sutjahjo; Setiyadi Setiyadi (Jurnal Poli-Teknologi, 2016)
ABSTRACT On the implementation of the construction project there is a contract which is the will to cooperate between the owner and the contractor, the contract was made in writing and agreed upon between the parties concerned aware of the rights and obligations of each. However, not infrequently, in the implementation of irregularities and discrepancies in the implementation process so that it can result in failure of the construction work. This study aimed to determine the cause of the failure of the construction work as well as how the solution from the aspect of the law against the failure of the construction work in the project implementation in Jakarta that could potentially be a dispute between the parties. Conclusions from the study include: Failure of construction work in the implementation of the project according to the order of the number of occurrences are the jobs structure: construction, foundation, frame and roof cover, earthworks construction, architecture of, for building utilities. The factors causing the failure of construction works in the project implementation in order of the number of occurrences are due to: the working methods of construction work and the project location, building design, materials used tool to support the implementation of projects, human resources, contracts and irregularities of construction work. While the completion of a failure in the execution of construction works for the parties in terms of the legal aspects are: the legal settlement of the dispute between the parties generally accomplished by means of deliberation, in mediating the settlement of disputes can use a third part. Keywords: Failure, work, construction, legal aspects